2015
DOI: 10.1111/mmi.12912
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial signal transduction protein GlnB regulates the committed step in fatty acid biosynthesis by acting as a dissociable regulatory subunit of acetyl‐CoA carboxylase

Abstract: SummaryBiosynthesis of fatty acids is one of the most fundamental biochemical pathways in nature. In bacteria and plant chloroplasts, the committed and ratelimiting step in fatty acid biosynthesis is catalyzed by a multi-subunit form of the acetyl-CoA carboxylase enzyme (ACC). This enzyme carboxylates acetyl-CoA to produce malonyl-CoA, which in turn acts as the building block for fatty acid elongation. In Escherichia coli, ACC is comprised of three functional modules: the biotin carboxylase (BC), the biotin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 47 publications
3
83
0
Order By: Relevance
“…Disturbance of ACC regulation has been shown to impact the acetyl-CoA pool (Davis et al, 2000; Zha et al, 2009). Recent findings showed that ACC in Arabidopsis thaliana and Escherichia coli is regulated additionally through interaction of BCCP with the P II protein GlnB (Feria Bourrellier et al, 2010; Gerhardt et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Disturbance of ACC regulation has been shown to impact the acetyl-CoA pool (Davis et al, 2000; Zha et al, 2009). Recent findings showed that ACC in Arabidopsis thaliana and Escherichia coli is regulated additionally through interaction of BCCP with the P II protein GlnB (Feria Bourrellier et al, 2010; Gerhardt et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…NrPII proteins are implicated in the regulation of primary carbon metabolism, as well. In land plants and bacteria, a central carbon metabolic enzyme acetyl-CoA carboxylase is directly regulated by nrPIIs 64,65 . In cyanobacteria, nrPIIs are thought to regulate nitrogen assimilation in a carbon-dependent manner 63,66 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was also observed that E. coli GlnB can modulate the activity of an enzyme dedicated to the carbon metabolism, i.e., acetyl-CoA carboxylase (ACC) (56).…”
Section: The P II Protein Familymentioning
confidence: 99%
“…3). The BCCP-P II interaction and ACC inhibition are relieved by 2-OG in a dosedependent manner (56). Hence, P II acts as a 2-oxoglutarate-sensitive dissociable regulatory subunit of ACC (Fig.…”
Section: The P II Protein Familymentioning
confidence: 99%